2023
DOI: 10.2147/prbm.s407744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alexithymia on Moral Decision-Making in Sacrificial Dilemmas: High Alexithymia is Associated with Weaker Sensitivity to Moral Norms

Abstract: Purpose Although several studies have investigated the association between alexithymia and moral decision-making in sacrificial dilemmas, the evidence remains mixed. The current work investigated this association and how alexithymia affects moral choice in such dilemmas. Methods The current research used a multinomial model (ie, CNI model) to disentangle (a) sensitivity to consequences, (b) sensitivity to moral norms, and (c) general preference for inaction versus actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Taken together, these findings suggest that individuals with a higher number of ACEs tend to exhibit more utilitarian responses, attributed to their reduced sensitivity to norms rather than heightened sensitivity to consequences or general action tendencies. 26 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these findings suggest that individuals with a higher number of ACEs tend to exhibit more utilitarian responses, attributed to their reduced sensitivity to norms rather than heightened sensitivity to consequences or general action tendencies. 26 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…However, their cognitive evaluation of outcomes and general action tendencies do not appear to be enhanced, as indicated by results concerning the C and I parameters. 26 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following study further quantifies the factors that influence moral dilemma judgements. The findings suggested that, regardless of moral standards and repercussions, the influence of alexithymia on moral choice suggests that the utilitarian choice and general behavioral outcome are comparable under this circumstance [9]. The change is in the deontological choice.…”
Section: Retps 2023mentioning
confidence: 94%
“…The first study asked a group of volunteers to complete an electronic questionnaire for the purposes of examining whether participants with advanced alexithymia were more likely than those who did not have this disease to prefer proactive responses over deontology. Consequently, people with inability to recognize one's emotion showed a preference for responses what are useful and practical [9]. They also investigated sensitivity to moral standards and a general tendency of no actions in all outcomes and norms.…”
Section: Retps 2023mentioning
confidence: 99%